Recent Advances in the Treatment of Ocular Complications of Rheumatoid Arthritis: A review of current literature - Duchnevič, Olgerd; Galasińska, Iwona; Michalik, Beniamin; Hajduk-Maślak, Katarzyna; Szypuła, Aleksandra; Sęk, Michał; Skóra, Adrianna (Journal of Education, Health and Sport, 2024)
Introduction: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that often causes ocular complications, of which keratoconjunctivitis sicca (KCS), scleritis and episcleritis are the most common entities. When left untreated, they can adversely affect eye health and cause vision loss in severe cases. Therefore, early and effective treatment of ophthalmic complications may significantly improve visual outcomes in patients with rheumatoid arthritis. Aim of the study: The aim of the study was to compile and analyze the current literature on the treatment of the most prevalent ocular manifestation associated with RA. Special emphasis was placed on recently approved drugs and those in late-stage clinical trials. Methods and materials: Publication research was conducted using the PubMed database and Google Scholar with a primary focus on literature from the past 10 years. Firstly, common ocular complications of rheumatoid arthritis were identified and relevant treatment modalities were extracted for further analysis. Finally, the names of relevant drugs or drug classes were used along with the names of the aforementioned disease entities to discover clinical trials regarding their efficacy and safety. Additionally, references from selected manuscripts were included. Summary: The landscape of treatment for ocular complications associated with RA offers a promising future for patients and clinicians. Three new therapeutic modalities for dry eye disease have been approved in 2023, and three additional drugs are in late-stage clinical trials. Furthermore, recent advances in biologic therapy have shown considerable promise in treating scleritis, especially in patients refractory to conventional treatment or with severe symptoms of the disease.